(untitled) - OMS (Genève, 1996)
"The World Health Report 1995", based on the most authoritative and up-to-date information gathered by the World Health Organization, explores the burden imposed by specific diseases and other health problems throughout the world in all the age groups, from children and adolescents to adults and the erderly. By presenting and analysing a wealth of new data, the report provides an expert and comprehensive diagnosis of the state of human health worldwide. More than that, it offers a prescription for action that could save millions of lives every year, and improve the quality of life for humanity
Keywords: health policy,health status,world health,world health organization; trends